2005
DOI: 10.1021/ef0498059
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Release and Catalytic Removal of Organic Sulfur Compounds from Upper Freeport Coal

Abstract: The tetrahydrofuran/carbon disulfide (THF/CS2) mixed solvent-insoluble portion of Upper Freeport coal was subject to noncatalytic and nickel-catalyzed hydrothermal treatments under pressurized hydrogen at 300 °C. The petroleum ether (PE)-soluble fractions from the reaction mixtures were analyzed using gas chromatography (GC) and gas chromatography/mass spectroscopy (GC/MS). Twenty-two organic sulfur compounds (OSCs) were detected in the PE-soluble fraction from the reaction mixture of noncatalytic hydrothermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…It is well known that benzo [20,21]hopanes 4−7 (C 32−35 , 2) and benzo [16,17,21]hopanes 6,8,9 (C 31−35 , 3) are formed from compound 1 via the cyclization reactions at C20 and C16, respectively. Some compounds with fluorene and acenaphthene moieties (e.g., compounds 4 and 5) in coals should be partially produced from D-ring monoaromatic 8 (14)-secobenzo [20,21]hopanes 6,10,11 (C 32−35 , 6) and 8 (14)-secobenzo [16,17,21]hopanes 11,12 (C 31−35 , 7), which are produced from the corresponding benzohopanes (i.e., compounds 2 and 3) via aromatization and C8−C14 bond cleavage, respectively. Coals are rich in the compounds with two aromatic moieties linked by −(CH 2 ) n −, such as 1-benzylnaphthalene ( 8), but their origin is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that benzo [20,21]hopanes 4−7 (C 32−35 , 2) and benzo [16,17,21]hopanes 6,8,9 (C 31−35 , 3) are formed from compound 1 via the cyclization reactions at C20 and C16, respectively. Some compounds with fluorene and acenaphthene moieties (e.g., compounds 4 and 5) in coals should be partially produced from D-ring monoaromatic 8 (14)-secobenzo [20,21]hopanes 6,10,11 (C 32−35 , 6) and 8 (14)-secobenzo [16,17,21]hopanes 11,12 (C 31−35 , 7), which are produced from the corresponding benzohopanes (i.e., compounds 2 and 3) via aromatization and C8−C14 bond cleavage, respectively. Coals are rich in the compounds with two aromatic moieties linked by −(CH 2 ) n −, such as 1-benzylnaphthalene ( 8), but their origin is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Organosulfur compounds (OSCs) in coals are the main source of air pollutants during coal combustion. , Hence, understanding of the types of OSCs in coals is of great importance for sulfur removal and subsequent clean use of coals . A number of researchers investigated the types of OSCs by various analytical methods, and many OSCs, such as cyclohexanethiol, benzenethiol, alkyldibenzothiophenes, ,, and alkylbenzonaphthothiophenes, , were detected from coals. However, to our knowledge, few reports were issued on the isolation and identification of sulfur-containing hopanoids, including 30-(5-methylthien-2-yl)­hopane ( 11 ) and 30-(thien-2-ylmethyl)­hopane ( 12 ), from coals.…”
Section: Introductionmentioning
confidence: 99%
“…A series of heterocyclic aromatics (HCAs) were detected in the PEEF from SFSBC (Ouyang et al, 2007) rather than from LR SFSBC . Significant amounts of HCAs in SFSBC could be converted via removal of heteroatoms (Sun et al, 2005;Fan et al, in press) and volatile HCAs could be transferred into oils, including heavy oil (Huang et al, 2009;Huang et al, 2011) during CHL of coals.…”
Section: Resultsmentioning
confidence: 99%
“…Murti et al () found that SCCs in a coal liquid distillate were almost completely removed by hydro‐desulfurization over a NiMoS/Al 2 O 3 catalyst at 360 °C, only trace amount of C 2 ‐benzothiophene and C 3 ‐benzothiophene remaining. Sun et al () reported a series of SCCs released from non‐catalytic hydrotreatment of modified Upper Freeport coal, including thiols, sulfides, disulfides, and trisulfides. They found that the sulfur in these SCCs can be efficiently removed through nickel‐catalyzed hydrotreatment at 300 °C and the related mechanisms for desulfurization were discussed.…”
Section: Small‐molecular Chemicals In Cdls Identified By Gc/msmentioning
confidence: 99%